2004
DOI: 10.1097/00002060-200406000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injection Skills Competency in Physical Medicine and Rehabilitation Residents

Abstract: An educational module was developed in attempt to satisfy two main objectives: to develop and implement a methodology for instruction of generally encountered injection techniques in the practice of physical medicine and rehabilitation and to implement an objective assessment format to measure attainment of these skills. Guidelines for this module were developed in consideration of Accreditation Council for Graduate Medical Education (ACGME) physical medicine and rehabilitation residency program requirements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…According to some theories [45,47,48], even if the issue is still controversial, recovery of movements from stroke in the upper extremity begins with the development of a flexor synergy (shoulder abduction-elbow flexion) followed by an extensor synergy (shoulder adduction- elbow extension) pattern [49], while isolated joint movements remain still compromised. This may result into the disruption of movement in terms of the required interjoint coordination.…”
Section: Discussionmentioning
confidence: 99%
“…According to some theories [45,47,48], even if the issue is still controversial, recovery of movements from stroke in the upper extremity begins with the development of a flexor synergy (shoulder abduction-elbow flexion) followed by an extensor synergy (shoulder adduction- elbow extension) pattern [49], while isolated joint movements remain still compromised. This may result into the disruption of movement in terms of the required interjoint coordination.…”
Section: Discussionmentioning
confidence: 99%
“…30 Aggregate results from 28 trials (1973 combined participants) comparing intraarticular corticosteroids vs placebo, hyaluronidate, joint lavage, or other corticosteroids showed that intra-articular corticosteroids were more effective for pain reduction and patient global assessment at 1 week (number needed to treat, [3][4] and that pain reduction lasted for 2 to 3 weeks. However, evidence for functional improvement with corticosteroids was lacking, and at 4 to 24 weeks after injection, no evidence was found for improvement in pain or function.…”
Section: Musculoskeletal Injection For Specific Anatomic Regions: CLImentioning
confidence: 99%
“…Although musculoskeletal injection is one of the most frequently performed procedures among practicing internists, 2 physicians receive inadequate training regarding musculoskeletal diseases and injection technique. [3][4][5][6] The Accreditation Council for Graduate Medical Education 7 and the American Board of Internal Medicine 8 require resident physicians to understand arthrocentesis, yet residency training programs have traditionally provided limited instruction on this topic. Consequently, some training programs have instituted special musculoskeletal curricula that have been shown to improve physicians' confidence and ability with joint injections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Simulation-based learning provides a low risk, predictable, and reproducible environment that has been embraced as a solution to teach learners new procedures without compromising patient safety. 5,6 Many studies, [7][8][9][10][11] including a few that specifically examined teaching arthrocentesis and intra-articular injection techniques, report preintervention to postintervention increases in…”
Section: Introductionmentioning
confidence: 99%